2022
DOI: 10.3389/fmed.2022.792238
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram and Machine Learning Models Predict 1-Year Mortality Risk in Patients With Sepsis-Induced Cardiorenal Syndrome

Abstract: ObjectiveEarly prediction of long-term outcomes in patients with sepsis-induced cardiorenal syndrome (CRS) remains a great challenge in clinical practice. Herein, we aimed to construct a nomogram and machine learning model for predicting the 1-year mortality risk in patients with sepsis-induced CRS.MethodsThis retrospective study enrolled 340 patients diagnosed with sepsis-induced CRS in Shanghai Tongji Hospital between January 2015 and May 2019, as a discovery cohort. Two predictive models, the nomogram and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Combining these variables in a model improved the AUC of the predictive curve. 18 However, the inclusion of the SOFA score, which assesses multiple organ systems simultaneously, may introduce overlap and potentially yield inaccurate results. Other studies have also demonstrated successful prognostic predictions by excluding the SOFA score.…”
Section: Discussionmentioning
confidence: 99%
“…Combining these variables in a model improved the AUC of the predictive curve. 18 However, the inclusion of the SOFA score, which assesses multiple organ systems simultaneously, may introduce overlap and potentially yield inaccurate results. Other studies have also demonstrated successful prognostic predictions by excluding the SOFA score.…”
Section: Discussionmentioning
confidence: 99%
“…Nomogram is a traditional calculation tool that includes variables and corresponding scoring lines. However, complex ML methods can manage a broader array of variables, often yielding more accurate and precise results than traditional modeling methods 21 . Additionally, one of the main challenges in applying MPP prediction models to clinical practice is the lack of external validation [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%